Land and temple as structural and thematic marks of coherence for the Hebrew edition of the Book of the Twelve - Morgan, David M. (Biblische Notizen, 2010)
Questions regarding whether the Book of the Twelve (Dodekapropheton) should be read as just that – a “book” – are more frequently asked by scholars in recent years. This article argues that the Twelve can be read as a “unity” (based upon ancient manuscript evidence) and a “coherence” (based upon the present prophetic corpus) by means of a reading program that evinces the leitmotifs of “land” and “temple”. From Hosea to Malachi, the Hebrew edition of the Twelve is an arrangement that reflects a temple building story for Persian Yehud.